2014
DOI: 10.3892/ol.2014.2195
|View full text |Cite
|
Sign up to set email alerts
|

A1BG and C3 are overexpressed in patients with cervical intraepithelial neoplasia III

Abstract: The present study aimed to analyze sera proteins in females with cervical intraepithelial neoplasia, grade III (CIN III) and in healthy control females, in order to identify a potential biomarker which detects lesions that have a greater probability of cervical transformation. The present study investigated five sera samples from females who were Human Papilloma Virus (HPV) 16+ and who had been histopathologically diagnosed with CIN III, as well as five sera samples from healthy control females who were HPV-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Functional annotation of A1BG is yet poorly understood, although it is overexpressed in several types of cancer, including CRC [56,57], and is ubiquitously expressed in many tissues under normal conditions. While studying CRC, A1BG has been observed to be abundant vesicles, suggesting its role in modulation of the immune response during cancer development [58]. The A1BG protein shows significant homology with immunoglobulin family proteins.…”
Section: Repercussion Of Proteins With Widely Proposed and Yet To Be mentioning
confidence: 99%
“…Functional annotation of A1BG is yet poorly understood, although it is overexpressed in several types of cancer, including CRC [56,57], and is ubiquitously expressed in many tissues under normal conditions. While studying CRC, A1BG has been observed to be abundant vesicles, suggesting its role in modulation of the immune response during cancer development [58]. The A1BG protein shows significant homology with immunoglobulin family proteins.…”
Section: Repercussion Of Proteins With Widely Proposed and Yet To Be mentioning
confidence: 99%
“…We found that alpha-1-B-glycoprotein (A1BG) and T4 surface glycoprotein precursor (TSGP) were both up-regulated in DEW and SP, and the expression was over two-fold higher in SP than DEW (Figure 1; Table 1). A1BG was reportedly involved in a number of diseases such as endometrial cancer, cervical cancer and cervical squamous cell carcinoma (30), and was also elevated in hepatic fibrosis patients, which allowed such patients to be easily distinguished from HI (31). TSGP was associated with T-cell costimulation, positive regulation of interleukin-2 biosynthesis, T-cell receptor complex formation, extracellular matrix structural constituents, the transmembrane receptor protein tyrosine kinase signaling pathway, early endosomes, innate immune responses, and proteinaceous extracellular matrix and MHC class II protein complexes.…”
Section: Glycoproteinsmentioning
confidence: 99%
“…The blots were washed three times with TBST and an enhanced chemiluminescence system (ImageQuant LAS 4000 mini; GE Healthcare Japan, Tokyo, Japan) was used to detect the bands. The band densities of PARP and Bcl-xL were measured with ImageJ (National Institutes of Health, Bethesda, MD, USA), and densitometry analysis was performed as previously described ( 24 ).…”
Section: Methodsmentioning
confidence: 99%